Five contemporary Indian novelists : an anthology of critical studies on Mulk Raj Anand, Raja Rao, R.K. Narayan, Kamala Markandaya, and Bhabani Bhattacharya - Singh, P. K. (Book Enclave, 2001)
Contributed essays.